Degradation and Recycling of Films Based on Biodegradable Polymers: A Short Review - Scaffaro, Roberto (Polymers (Basel), 2019)
The environmental performance of biodegradable materials has attracted attention from the academic and the industrial research over the recent years. Currently, degradation behavior and possible recyclability features, as well as actual recycling paths of such systems, are crucial to give them both durability and eco-sustainability. This paper presents a review of the degradation behaviour of biodegradable polymers and related composites, with particular concern for multi-layer films. The processing of biodegradable polymeric films and the manufacturing and properties of multilayer films based on biodegradable polymers will be discussed. The results and data collected show that: poly-lactic acid (PLA), poly-butylene adipate-co-terephthalate (PBAT) and poly-caprolactone (PCL) are the most used biodegradable polymers, but are prone to hydrolytic degradation during processing; environmental degradation is favored by enzymes, and can take place within weeks, while in water it can take from months to years; thermal degradation during recycling basically follows a hydrolytic path, due to moisture and high temperatures (β-scissions and transesterification) which may compromise processing and recycling; ultraviolet (UV) and thermal stabilization can be adequately performed using suitable stabilizers.